2009
DOI: 10.1007/s00125-009-1451-3
|View full text |Cite
|
Sign up to set email alerts
|

Impaired regulation of the TNF-α converting enzyme/tissue inhibitor of metalloproteinase 3 proteolytic system in skeletal muscle of obese type 2 diabetic patients: a new mechanism of insulin resistance in humans

Abstract: Aims/hypothesis TNF-α levels are increased in obesity and type 2 diabetes. The regulation of TNF-α converting enzyme (TACE) and its inhibitor, tissue inhibitor of metalloproteinase 3 (TIMP3), in human type 2 diabetes is unknown. Methods We examined TACE/TIMP3 regulation: (1) in lean and obese normal glucose tolerant (NGT) individuals and in type 2 diabetes patients; (2) following 6 h of lipid/ saline infusion in NGT individuals; and (3) in cultured human myotubes from lean NGT individuals incubated with palmit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(62 citation statements)
references
References 51 publications
2
57
0
3
Order By: Relevance
“…sortilin reduction to be mediated at least partially through the post-translational modification (shedding) involving TACE activity (25), which could be activated by a PKC activator, TPA (26). Intriguingly, several recent studies have demonstrated that TACE activity is increased in the skeletal muscles of obese type 2 diabetes patients and in lipid-induced insulin resistance (43,44). In addition, increased TACE activity has been directly implicated in the pathogenesis of insulin resistance, which is generally explained by the augmented secretion of TNF-␣ (43,45,46).…”
Section: Discussionmentioning
confidence: 99%
“…sortilin reduction to be mediated at least partially through the post-translational modification (shedding) involving TACE activity (25), which could be activated by a PKC activator, TPA (26). Intriguingly, several recent studies have demonstrated that TACE activity is increased in the skeletal muscles of obese type 2 diabetes patients and in lipid-induced insulin resistance (43,44). In addition, increased TACE activity has been directly implicated in the pathogenesis of insulin resistance, which is generally explained by the augmented secretion of TNF-␣ (43,45,46).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that Type 1 diabetes is associated cancer risk in a population-based study (Zendehdel et al, 2003). It is well accepted that infl ammation is closely associated with diabetes: TNF-α converting enzyme (TACE) activity as well as TNF-α is increased in diabetic patients (Fornoni et al, 2008;Monroy et al, 2009). Considering the fact that shedding of syndecan-1 is paralled by TNF-α release, it is possible that diabetes could be lead to cancer development via TACE and TNF-α system (Andrian et al, 2005).…”
Section: Diabetes and Cancermentioning
confidence: 99%
“…In humans with metabolic disorders, such as obesity and type 2 diabetes, the co-occurrence of lipotoxicity and glucotoxicity has been found to increase the ADAM17 activity by decreasing the tissue inhibitor of metalloproteinase 3 (TIMP3) expression, while an increased ADAM17 activity has been reported to correlate with insulin resistance 31) . Therefore, ADAM17 …”
Section: Effects Of Adam17 Gene Polymorphisms On the Adam17 Expressionmentioning
confidence: 99%
“…In humans with metabolic disorders, such as obesity and type 2 diabetes, the co-occurrence of lipotoxicity and glucotoxicity has been found to increase the ADAM17 activity by decreasing the tissue inhibitor of metalloproteinase 3 (TIMP3) expression, while an increased ADAM17 activity has been reported to correlate with insulin resistance 31) . Therefore, ADAM17 Therefore, the rs1524668 ADAM17 polymorphism is likely to be one a key determinant of an increased occurrence of the PACI stroke subtype, while elevation of the ADAM17 mRNA expression confirms the role of ADAM17 in the pathophysiology of IS, with potentially important therapeutic implications.…”
mentioning
confidence: 99%